The Utilization of the Cobb-Douglas Production Function for Analyzing Indonesia's and Malaysia's Economic Growth - Elis Ratna Wulan (UIN Sunan Gunung Djati Bandung, 2013)
This paper presents the utilization Cobb-Douglas production function in its classical form for analyzing Indonesia's and Malaysia's economic growth in relation to the intensity of using capital and labour as determinants of the production.